Molecular Structure Effects on the Aggregation Motif of Porphyrins: Computational Insights. Issue 6 (4th May 2021) - Politi, Antiope T.; Politis, Achilleas; Seton, Linda
Abstract: The latest advancements in semiempirical Hamiltonians have inspired new confidence for the supramolecular computational predictivity. The advanced accuracy of newly developed semiempirical methods is offered for computations of what can provide a valuable database of molecular tuning recommendations for the synthesis of new supramolecular materials. In this work the very versatile and impactful porphyrin is employed for examination of the first basic chemical tuning factors that may drive specific aggregation motifs. The 1D motifs are examined as a function of peripheral substituent steric bulk. Subsequently, a 1D‐wire versus a 3D‐square motif is investigated as a function of the metal–ligand effect. For the first time, an interesting effect of misprediction of semiempirical computations is encountered for a small class of these aggregates and is briefly examined with a conformational search analysis. These findings encourage further in silico work which is greatly required for diminishing the current discovery bottleneck in supramolecular chemistry. Abstract : Chemical tuning in self‐assembly: The peripheral functionalisation of poprhyrinic mer units leads to drastic changes in supramolecular assembly motif. The fine supramolecular architectural details and degree of dimentionality can be controlled with the appropriate choice of peripheral substituents in the mer units. Fast systematic predictions are made with GFN2‐xTB.